2020
DOI: 10.1371/journal.pone.0241536
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of asymptomatic infection among COVID-19 positive persons and their transmission potential: A systematic review and meta-analysis

Abstract: Background The study objective was to conduct a systematic review and meta-analysis on the proportion of asymptomatic infection among coronavirus disease 2019 (COVID-19) positive persons and their transmission potential. Methods We searched Embase, Medline, bioRxiv, and medRxiv up to 22 June 2020. We included cohorts or cross-sectional studies which systematically tested populations regardless of symptoms for COVID-19, or case series of any size reporting contact invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
239
4
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(262 citation statements)
references
References 71 publications
11
239
4
8
Order By: Relevance
“…Higher age may correlate with the development of typical clinical symptoms of COVID-19 [ 19 ]. A recent meta-analysis found that in obstetric patients, 95% (45–100%) of SARS-CoV-2 infections were asymptomatic, whereas asymptomatic SARS-CoV-2 infection among nursing home residents occurred in 54% (42–65%) of patients [ 20 ] supporting a higher proportion of asymptomatic courses among younger age groups. High proportions of asymptomatic infections in both young and elderly people were found in an analysis of SARS-CoV-2 outbreaks in six care homes in Great Britain.…”
Section: Discussionmentioning
confidence: 99%
“…Higher age may correlate with the development of typical clinical symptoms of COVID-19 [ 19 ]. A recent meta-analysis found that in obstetric patients, 95% (45–100%) of SARS-CoV-2 infections were asymptomatic, whereas asymptomatic SARS-CoV-2 infection among nursing home residents occurred in 54% (42–65%) of patients [ 20 ] supporting a higher proportion of asymptomatic courses among younger age groups. High proportions of asymptomatic infections in both young and elderly people were found in an analysis of SARS-CoV-2 outbreaks in six care homes in Great Britain.…”
Section: Discussionmentioning
confidence: 99%
“…The unknown number of asymptomatic COVID-19-positive patients was probably underestimated, especially at the beginning of the pandemic [ 24 ]. Elective procedures are being performed again, and the discipline required for testing, maintaining distance from contacts, and limiting social interaction may drop.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 patients might be asymptomatic or symptomatic and when symptomatic they might present with conditions of mild-to-severe respiratory difficulties which might even necessitate admission to the intensive care unit. 3 A systematic review by Yanes-Lane et al 4 has shown a higher proportion of asymptomatic infection in COVID-19 patients with significantly higher transmission potential.…”
Section: Introductionmentioning
confidence: 99%